(untitled) (Medico Legal Update, 2021)
Background: Thoracic epidural anesthesia for LC is a satisfactory alternative technique in selected cases, therefore aim of current study was compare the deference between using of bupivacaine 0.5% at one and bupivacaine 0.5%. With sodium Bicarbonate 8.4 %. The differences we deal with there are onset of action. Duration of action, Potency, and the occurrence of complications. We report the sex, Age and smoking to see we these factors can affecting the study ornot. Patients and Method: The sample contain 2 groups of patient each group involved 20 patent with deferent age and sex. Group A receive Bupivacaine 0.5% 12ml alone for thoracic epidural anesthesia at level of T6 for laparoscopic. Cholecystectomy while ingroup B, we give Bupivacaine 0.5% 12ml with sodium bicarbonate 8.4 % 5ml (420mg) for the same operation at the same level of injection. In both groups we put the epidural catheter for addition of more dose of Bupivacaine and the mixture if the action of drug is finish and for the postoperative pain management after the operation.